Lipid profile in breast cancer patients: A case-control study done at a public tertiary hospital in Ibadan Nigeria - Adeniyi Adedayo Olabumuyi; Abbas Adesina Abdus-Salam; Babatunde Olutoye Ogunnorin; Modupe Akinrele Kuti (Nigerian Journal of Medicine, 2021)
Background: Breast cancer, the leading malignancy among women in Nigeria in terms of incidence and mortality, contributes a greater proportion of cancer burden compared with other cancers in Nigeria. A need to further identify and modify risk factors of breast cancer is necessary to apply preventive medicine and decrease its disease burden. Serum lipid profile is an objective index of fat metabolism, but its relationship with breast cancer is yet to be extensively investigated in our environment. Aim: To explore the relationship of serum lipid profile with breast cancer in the University College Hospital, Ibadan. Methods: The anthropometry, body fat percentage and lipid profile of 70 patients with breast cancer and 71 age-matched controls were studied. Statistical Analysis: Differences in the mean values of the lipid profile parameters were tested for significance using the Student's t-test and Mann–Whitney U test. Results: The breast cancer patients had statistically significantly higher serum triglyceride (TG) and very low-density lipoprotein cholesterol (P < 0.001). This was also an independent risk factor with multivariate analysis. Demonstrating the odds of breast cancer rose by 5.1% (odds ratio = 1.051, P < 0.001) with each 1 mg/dl rise in serum TG. Conclusion: There is potential for serum TG to be utilized as a marker of breast cancer. However, this needs to be determined by more elaborate studies.